The Historical Taboo: Colonial Discourses and Postcolonial Identities in Belgium - Bobineau, Julien (Werkwinkel, 2017)
This article examines so-called colonial discourses in Belgium related to the former Sub-Saharan colony owned by Leopold II of Belgium which today is known as the Democratic Republic of Congo (DR Congo) or the Congo-Kinshasa. Having introduced the colonial history of the DR Congo from the 15th century until 1910, the study starts with a discussion of Van den Braembussche’s concept of a ‘historical taboo’ and four ways of engaging with such implicit interdictions. Finally, an empirical analysis of colonial discourses in Belgium from the 1890s until today will be presented in conjunction with Belgium’s linguistic-cultural division, taking into account age-related divergence.